Clinical and Neuroimaging Profile of Children with Lesions in the Corpus Callosum. Issue 5 (18th December 2014) - Harini, Chellamani; Das, Rohit R.; Prabhu, Sanjay P.; Singh, Kanwaljit; Haldar, Amit; Takeoka, Masanori; Bergin, Ann M.; Loddenkemper, Tobias; Kothare, Sanjeev V.
ABSTRACT PURPOSE T2‐hyperintense signal changes in corpus callosum (CC) have been described in epilepsy and encephalitis/encephalopathy. Little is known about their pathophysiology. The aim of this study was to examine the clinical presentation and evolution of CC lesions and relationship to seizures. METHODS We identified 12 children among 29, 634 patients from Radiology Database. We evaluated following characteristics: seizures and accompanying medical history, antiepileptic drug usage, presenting symptoms, and radiological evolution of lesions. RESULTS CC lesions were seen in patients with prior diagnosis of epilepsy (n = 5) or in those with new onset seizures (n = 3), or with encephalitis/encephalopathy without history of seizures (n = 4). Seizure clustering or disturbances of consciousness were the main presenting symptoms. No relationship was observed between CC lesion and AEDs. On imaging, ovoid lesions at presentation resolved on follow up imaging and linear lesions persisted. DTI showed that the fibers passing through splenial lesions originated from the posterior parietal cortex and occipital cortex bilaterally. CONCLUSION In patients with seizures, no clear relationship was demonstrated between seizure characteristics or AED use with CC lesions. Ovoid lesions resolved and may have different pathophysiologic mechanism when compared to linear lesions that persisted.